Investigations of the dynamics of a bistable electromagnet with improved characteristics for medium voltage vacuum circuit breakers - Baida, Evgeniy Ivanovich; Klymenko, Boris Vladimirovich; Vyrovets, S. V.; Pantelyat, Michael G.; Clemens, M. (Національний технічний університет "Харківський політехнічний інститут", 2020)
Introduction. Currently, for switching medium voltage circuits, vacuum circuit breakers are widely used, which have good arcing properties and high breaking capacity. One of the problems of creating the drive mechanism of such apparatus is the need to ensure the absence of contact welding when a through current of a short circuit of a given duration flows through them, which is achieved due to a certain amount of contact pressure. One of the problems arising in the design of circuit breakers is the need to fix the mechanism with a mechanical lock, which should hold the mechanism securely. This leads to significant specific mechanical loads, which in turn reduces the reliability of the circuit breaker. One way to solve these problems is to create a drive based on monostable or bistable electromagnetic actuators with highly coercive permanent magnets, which provide reliable fixation of the position of the contacts. Purpose. Investigation of the improved design of a bistable electromagnetic actuator based on permanent magnets of a medium voltage vacuum circuit breaker. Methods. Theoretical and experimental research and comparative analysis of existing and developed electromagnetic actuators. Conclusions. A new design of an electromagnetic bistable actuator with reduced overall dimensions is developed and tested. The electromechanical characteristics of the actuator correspond to the technical specifications, which is confirmed by both theoretical and experimental studies. The proposed actuator can be used as a drive mechanism for medium voltage vacuum circuit breakers.

В статье исследован новый бистабильный электромагнит с высококоэрцитивными постоянными магнитами, который предполагается использовать в качестве актуатора вакуумных выключателей средних напряжений. Приводится теоретическое и экспериментальное исследование усовершенствованной конструкции электромагнита с целью сравнительного анализа его параметров с параметрами имеющейся конструкции. Теоретическое исследование базируется на мультифизической модели, которая включает расчет статического и динамического электромагнитных полей в нелинейной проводящей неоднородной среде с учетом постоянных магнитов, нелинейных уравнений разрядной цепи накопительного конденсатора, нелинейных уравнений движения. Экспериментальные исследования, которые проводились на реальном вакуумном выключателе, показали соответствие параметров нового бистабильного электромагнита расчетным показателям. Направление дальнейших исследований представляются в виде оптимизации геометрии электромагнита и схемы управления.
Keywords: actuator; multiphysics model; актуатор; мультифизическая модель